Notes from the field: doing research on life narratives and wisdom-fostering life events among Turkish septuagenarians+ - Gezgin, Ulaş Başar; Işık, Sefer Yetkin; Işık, Sefer Yetkin (Senex: Yaşlılık Çalışmaları Dergisi, 2019)
This short piece which is written in the format of the notes from the field discusses plans to do life narratives and wisdom research among Turkish older adults. The starting point was a brief literature review of gerontology-related research in Turkey which will not be presented here due to space limitations. Secondly, the site and accordingly the sample of the anthropological study had to be decided. Thirdly, international gerontology-related research was reviewed to decide on theoretical discussions, methodology and conceptual tools to analyze the data. The notes conclude with a proposal for research in gero-narratology which is proposed to be the study of the structural and authorship properties of older adults' narratives.

Alandan notlar formatında yazılmış bu kısa yazı, Türkiyeli yaşlılarla yaşam anlatıları ve bilgelik araştırmaları yapma planlarını tartışmaktadır. Başlangıç noktası, Türkiye’de gerontolojiyle ilgili araştırmaların kaynak taramasıydı; ancak bu tarama, yer darlığı nedeniyle burada paylaşılmayacak. İkinci olarak, antropoloji çalışmasının yeri ve buna bağlı olarak örneklemi konusunda bir karara varılmalıydı. Üçüncü olarak, gerontolojiyle ilgili uluslararası araştırmalar, kuramsal tartışmalar, yöntembilim ve verileri çözümlemek için gerekli kavramsal araçlara karar vermek üzere gözden geçirildi. Notlar, yaşlıların anlatılarındaki yapısal özellikleri ve yazarlık özelliklerini çalışan bir alan olması öne sürülen gero-anlatıbilim ya da yaşlı anlatıbilimi alanında bir araştırma önerisiyle noktalanıyor.
Keywords: Antropo-gerontoloji; Anthropo-gerontolgy; Antropoloji; Anthropological